Activism and academia: a borderland genealogy. Feminist, Gender and Women’s Studies in Mendoza - ciriza, alejandra (Centro Interdisciplinario de Investigaciones en Género. IdIHCS (CONICET - UNLP). Facultad de Humanidades y Ciencias de la Educación, Universidad Nacional de La Plata, 2017)
This paper aims to map the emergence of feminist, gender and women’s studies in Cuyo, describing the beginnings and the process that led to the achievement of fragile institutionalization. Our analysis appeals to the notion of women and feminist genealogies as an analytical tool, based on the surmise that there exists a relationship between ideas and material conditions of existence, as well as between women’s activism and feminist and gender studies. The methodology used implied the collection and analysis of bibliographical and documentary evidence. The work offers a description of the tensions between academia and feminist activism, while addressing some of the obstacles for the institutionalization of this academic field of research.